Clifford's valentines - Bridwell, Norman (New York : Scholastic, 2001)
Clifford, the big red dog, makes a snowy valentine for his friends.
"Cartwheel books."
Keywords: Valentines -- Fiction; Valentine's Day -- Fiction; Dogs -- Fiction